Analysis and quantification of flavonoidic compounds from Portuguese olive (Olea europeae L.) leaf cultivars - Meirinhos, Julieta (2008)
Twenty three samples of 18 Portuguese olive leaf cultivars were analysed by a reversed-phase HPLC/DAD procedure and eight flavonoidic compounds were identified and quantified (luteolin 7,40-O-diglucoside, luteolin 7-O-glucoside, rutin, apigenin 7-O-rutinoside, luteolin 40-O-glucoside, luteolin, apigenin and diosmetin). Luteolin 7,40-O-diglucoside and luteolin 40-O-glucoside were identified by HPLC/DAD/MS/MS – ESI. The studied olive leaf samples showed a common phenolic pattern, in which luteolin 40-O-glucoside was almost always the major compound